2012
DOI: 10.2174/1874210601206010153
|View full text |Cite
|
Sign up to set email alerts
|

“Pyogenic Granuloma - Hyperplastic Lesion of the Gingiva: Case Reports”

Abstract: Pyogenic granuloma is a reactive hyperplasia of connective tissue in response to local irritants. It is a tumourlike growth of the oral cavity, frequently located surrounding the anterior teeth or skin that is considered to be neoplastic in nature. It usually arises in response to various stimuli such as low-grade local irritation, traumatic injury, hormonal factors, or certain kinds of drugs. Histologically, the surface epithelium may be intact, or may show foci of ulcerations or even exhibiting hyperkeratosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 10 publications
(15 reference statements)
2
57
0
Order By: Relevance
“…Clinically, it is a tumor-like growth of the oral cavity, most often located around the anterior teeth. 19 The study of Dojcinovic et al 10 demonstrated the case of a man who had developed a PG due to the inadequate choice of a healing abutment, thus allowing an accumulation of plaque and chronic inflammation of the peri-implant tissue. Olmedo et al 4 histologically observed the presence of metal particles in biopsied GPs, suggesting that the etiology of the lesions may be related to the corrosion process of the metallic structure, as shown also by Rodrigues et al 9 GPCG is a relatively frequent benign reactive lesion of the oral cavity, originating from the periosteum or periodontal membrane, developed in response to local irritation or chronic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is a tumor-like growth of the oral cavity, most often located around the anterior teeth. 19 The study of Dojcinovic et al 10 demonstrated the case of a man who had developed a PG due to the inadequate choice of a healing abutment, thus allowing an accumulation of plaque and chronic inflammation of the peri-implant tissue. Olmedo et al 4 histologically observed the presence of metal particles in biopsied GPs, suggesting that the etiology of the lesions may be related to the corrosion process of the metallic structure, as shown also by Rodrigues et al 9 GPCG is a relatively frequent benign reactive lesion of the oral cavity, originating from the periosteum or periodontal membrane, developed in response to local irritation or chronic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically pyogenic granuloma seen as exophytic lesion with a pedunculated or sessile base and their size varies from few millimeters to several centimeters in size but rarely seen more than 2.5 cm [8] and rarely, may cause significant bone loss. [9] In present case the size of lesion attained unusual larger size which ranges from 5-6 cm and caused significant bone loss in affected area.…”
Section: Discussionmentioning
confidence: 99%
“…When surgical excision below the periosteum and removal of irritants are performed, the rate of recurrence of granuloma gravidarum is very low, comprising about 5% of cases 5 . Additionally, a careful management of the lesion should be performed at the same time to maintain and improve the mucogingival complex 28 .…”
Section: Discussionmentioning
confidence: 99%